2011
DOI: 10.1111/j.1365-2052.2011.02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in eggshell crystal size and orientation is large and these traits are correlated with shell thickness and are associated with eggshell matrix protein markers

Abstract: SummaryThe size and orientation of calcium carbonate crystals influence the structure and strength of the eggshells of chickens. In this study, estimates of heritability were found to be high (0.6) for crystal size and moderate (0.3) for crystal orientation. There was a strong positive correlation (0.65) for crystal size and orientation with the thickness of the shell and, in particular, with the thickness of the mammillary layer. Correlations with shell breaking strength were positive but with a high standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 28 publications
5
66
2
Order By: Relevance
“…The steady reduction in albumen quality with increased flock age has also been reported by several researchers (Williams 1992;Silversides 1994). The heritability of many egg quality parameters is high (Dunn 2011;Dunn et al 2012), which means that genetic selection by major breeding companies can assist with improvements in quality, in addition to management improvements. The use of MST cuticle blue stain for determining the extent of cuticle cover in avian egg shells has been verified by correlating the extent of staining with the appearance of the shell cuticle under the scanning electron microscope.…”
Section: Discussionmentioning
confidence: 99%
“…The steady reduction in albumen quality with increased flock age has also been reported by several researchers (Williams 1992;Silversides 1994). The heritability of many egg quality parameters is high (Dunn 2011;Dunn et al 2012), which means that genetic selection by major breeding companies can assist with improvements in quality, in addition to management improvements. The use of MST cuticle blue stain for determining the extent of cuticle cover in avian egg shells has been verified by correlating the extent of staining with the appearance of the shell cuticle under the scanning electron microscope.…”
Section: Discussionmentioning
confidence: 99%
“…stage (26 th most abundant protein, Figure 5C). Different studies in vivo demonstrated correlations between ovocalyxin-32 (OCX32) gene polymorphism and different eggshell quality phenotypes, such as eggshell strength or mammillary layer thickness [73][74][75][76][77], which support its involvement in the control of the crystal texture of the eggshell. Its overabundance at 7 hours p.o.…”
Section: Ovalbumin (Oval) Had Been Identified Previously In the Eggshmentioning
confidence: 98%
“…The chorioallantoic membrane provides a direct connection between the embryo and the egg, which allows for aerobic metabolism and the uptake of calcium by the embryo from the eggshell (Carpenter 1999). In addition, the aragonite structure of the eggshell is under direct genetic control (Rodriguez-Navarro et al 2007;Dunn et al 2012), and the embryo, yolk, albumin, membranes and mineralized eggshell form a single unit. As such, fossil eggs and eggshell offer insight into some of the earliest ontogenetic stages of extinct organisms and are occasionally augmented by data from identifiable embryonic remains and gravid females.…”
Section: Fossil Eggs: Trace Compared With Body Fossilsmentioning
confidence: 99%